Perbandingan Presentasi Belajar Mahasiswa yang Aktif Mengikuti Organisasi dengan Mahasiswa yang tidak Mengikuti Organisasi Angkatan 2020 Di Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Sumatera Utara - Alfina Damayanti; Miza Nina Adlini; Yuli Erpiyana Harahap; Raja Siti Aisyah; Yara Maulina Nasution; Tara Wardana (Tarbiatuna: Journal of Islamic Education Studies, 2024)
Student organizations that exist in tertiary institutions cause different activities for students, just as students who are active in organizations are students who take their time to participate in student organization activities, but do not leave the obligation to take part in lecture activities. The purpose of this study was to find out the comparisons or differences between students who actively participate in organizations and students who do not join organizations regarding the presentation of learning outcomes at the Faculty of Tarbiyah and Teacher Training Uinsu class of 2020. The research method uses a quantitative research approach, namely research whose analysis techniques emphasize data- data in the form of numbers and processed with statistical methods to show the relationship between variables. The research design uses a comparative research design (comparative). The data analysis technique used is descriptive quantitative statistics in the form of a student test ("t" test). The results showed that students who were not active in organizations scored higher than students who were active in organizations. However, there is no significant difference but the difference is not too far. Keywords: comparison of presentations, students, organizations, class of 2020